ANALISIS GANGGUAN PENDENGARAN TIPE SENSORINEURAL PADA PEKERJA AKIBAT KEBISINGAN DI INDUSTRI MEBEL KAYU DI KOTA PEKANBARU - Suryani Suryani; Aras Mulyadi; Dedi Afandi (Jurnal Ilmu Lingkungan, 2015)
A worker who works at a wood furniture industry has high-risk of a sensorineuralhearing loss because he/she is exposed to the noise which exceeds the threshold value.The present research was set to examine the relationship between the noise in theworkplace and a sesorineural hearing loss suffered by a wood furniture industry workerin Pekanbaru. The design of the research was cross sectional. The population consistedof 27 wood furniture industry workers and noise intensity sample was taken in aworkplace of planing and sawing unit at 11 wood furniture industries in Pekanbaru.The independent variables were age, noise intensity (dB), working period (year), dailywork length, the use of hearing protective device. The analysis is based on univariate,bivariate and multivariate and the calculation of prevalence ratio value. The resultsshow that there were two variables which had significant correlations withsensorineural hearing loss, namely working period 16 – 30 years (RP = 4.024; 95% CI= 1.476 – 10.971) and age 40 – 59 years (RP = 3.200; C1 = 1.547 – 6/619). Theanalyses also show that the prevalence of sensorineural hearing loss was very large(76.9%) when working period > 16 years and age > 40 years. Since the prevalence ofworkers with sensorineural hearing loss was high, Manpower and Health Offices weresuggested to do promotive and preventive efforts in order that safety and health of thewood furniture industry workers could bemaintained.